Fatal Septic Shock Associated with Herpes Simplex Virus Hepatitis: A Case Report - Valentine Inthasot; Adonis Goushchi; Silvia Lazzaroni; Alberto Papaleo; Maria Gomez Galdon; Didier Chochrad (European Journal of Case Reports in Internal Medicine, 2018)
Herpes simplex viruses are endemic worldwide, with an estimated seroprevalence of approximately 70% in developed countries. However, it is less well known that they are one of the viral causes of fulminant hepatitis (<2%) and constitute <1% of all causes of acute liver failure. We describe the case of an 89-year-old man who developed sepsis caused by a urinary tract infection due to drug-sensitive Escherichia coli. After empirical treatment with piperacillin-tazobactam was initiated, the patient’s condition worsened with shock, acute liver and renal failure, encephalopathy and persistent fever, that led to admission to the intensive care unit. The emergence of an acute abdomen prompted exploratory laparotomy but the patient died soon after surgery from abdominal haemorrhage. Immunohistochemical analysis of a liver biopsy specimen identified herpes simplex virus (HSV) hepatitis. The authors emphasize the need for better understanding of this rare condition in order to more precisely identify patients at risk who need more aggressive evaluation and empirical treatment, especially patients presenting with marked hepatic cytolysis with a rapidly worsening clinical evolution.